2003
DOI: 10.1136/bmj.326.7385.368
|View full text |Cite
|
Sign up to set email alerts
|

Dying from cancer in developed and developing countries: lessons from two qualitative interview studies of patients and their carers

Abstract: Objective To describe the experiences of illness and needs and use of services in two groups of patients with incurable cancer, one in a developed country and the other in a developing country. Results 67 interviews were conducted in Scotland and 46 in Kenya. The emotional pain of facing death was the prime concern of Scottish patients and their carers, while physical pain and financial worries dominated the lives of Kenyan patients and their carers. In Scotland, free health and social services (including fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
114
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(120 citation statements)
references
References 11 publications
4
114
1
1
Order By: Relevance
“…In a survey of terminally ill patients in five countries in Africa -Uganda, Ethiopia, Tanzania, Zimbabwe and Botswana -the greatest need expressed by the patients was pain relief. 62 In another study 63 comparing the concerns of terminally ill patients in a developed country RI [41][42][43][44][45][46][47][48][49] (Scotland) and an African country (Kenya), it was found that the main concern of the Scottish patients was the emotional pain of facing death, while for their counterparts in Kenya it was physical pain and financial worries. Unfortunately, there is inadequate availability of pain-relieving medications, especially opioids.…”
Section: Treatment Of Invasive Cervical Cancer: Palliative Carementioning
confidence: 99%
See 1 more Smart Citation
“…In a survey of terminally ill patients in five countries in Africa -Uganda, Ethiopia, Tanzania, Zimbabwe and Botswana -the greatest need expressed by the patients was pain relief. 62 In another study 63 comparing the concerns of terminally ill patients in a developed country RI [41][42][43][44][45][46][47][48][49] (Scotland) and an African country (Kenya), it was found that the main concern of the Scottish patients was the emotional pain of facing death, while for their counterparts in Kenya it was physical pain and financial worries. Unfortunately, there is inadequate availability of pain-relieving medications, especially opioids.…”
Section: Treatment Of Invasive Cervical Cancer: Palliative Carementioning
confidence: 99%
“…Unfortunately, there is inadequate availability of pain-relieving medications, especially opioids. [62][63][64][65] Only 11 out of 47 African countries use morphine for chronic pain and of these 11, the amount consumed is small. 64 Oral morphine is not available to very many cancer patients in sub-Saharan Africa.…”
Section: Treatment Of Invasive Cervical Cancer: Palliative Carementioning
confidence: 99%
“…Una revisión de la bibliografía especializada actual ofrece ejemplos de estudios basados en una exploración de la perspectiva de los usuarios, realizados con el objetivo de conocer el grado de satisfacción con el cuidado recibido 6,37 , las debilidades, fortalezas y creencias respecto a métodos de prevención 21,38,39 y detección precoz 5,13,18,20,40,41 , las expectativas respecto al papel de Atención Primaria 34,42,43 y Especializada 33,34,37,[44][45][46] , las necesidades psicosociales de los pacientes 10,34,36,[47][48][49] , así como de sus cuidadores informales 36,[49][50][51] . Partiendo de la observación de la relevancia de una inclusión de la perspectiva de los usuarios en el desarrollo de programas de mejora de la calidad en el proceso asistencial de cáncer, el presente estudio propone analizar las experiencias de pacientes de cáncer con la asistencia sanitaria recibida en Atención Primaria y Especializada en diferentes etapas…”
Section: Introductionunclassified
“…Timely access to palliative care services is an issue raised by a number of authors (Carter, McKinlay, Scott, Wise, & Mcleod, 2002;Finlay et al, 2002;Heilig, 2003;Massarotto, Carter, MacLeod, & Donaldson, 2000;Murray, Grant, Grant, & Kendall, 2005). In America, only 20-30% of people who are dying are receiving hospice services (Heilig, 2003), and as we discuss below, minority cultural groups in particular often do not access palliative care.…”
Section: Palliative Carementioning
confidence: 99%